Harry's farewell : interpreting and teaching the Truman presidency - Kirkendall, Richard Stewart, 1928- (University of Missouri Press, 2004)
"Harry's Farewell confronts the biggest issue of Truman historiography: the historical significance of Harry S. Truman's presidency. Exploring the subject from the point of view of Truman's Farewell Address of January 15, 1953, the book begins by describing the preparation of the address itself by the president and his closest advisers. In it, they challenged the negative view of his presidency that prevailed as he prepared to leave the White House. The book goes on to appraise the presidency in terms of the topics included in the address: the president and the people, the economy, civil rights, the bomb, Containment, Korea, and the end of the Cold War. Four essays follow that cover key topics that Truman did not mention in his speech: the Red Scare, women's rights, ethnicity, and the environment. The book ends with essays by two major Truman biographers who present their own interpretations of his historical significance."--Jacket.